Occupational Health & Safety Risk Analysis with HIRADC Method in Building Construction Project X - Fajar, Vidya Amelia; Soeryodarundio, Koosdaryani; Rifai, Muji (Sustainable Civil Building Management and Engineering Journal, 2024)
Within construction projects, there is a risk of workplace accidents that can cause injury and death to workers. These risks are some of the factors that can cause project failure and affect other worker activities. If proper risk control is no carried out the incident can escalate into a fatal work accident. Therefore, good implementation of Occupational Safety and Health (OHS) is essential in every construction project. This research aims to plan work safety using Hazard Identification, Risk Assessment, and Determining Control (HIRADC) method to identify potential hazards, assess the risk of these hazards, and determine appropriate controls to minimize the risks that may occur. In the observed work, the result of hazard identification and risk assessment using the HIRADC method found 22 potential hazards, namely 3 with extreme risk level, and 5 with low risk level. Control were carried out based on the control hierarchy in the form of engineering, administrative, and personal protective equipment (PPE), which succeeded in reducing the risk level so that there were no jobs with extreme and high risk levels. Thus, it can be understood that proper risk control can prevent work accidents.